The complex genetic landscape of southwestern Chinese populations contributed to their extensive ethnolinguistic diversity - Wang, Mengge; Duan, Shuhan; Sun, Qiuxia; Liu, Yan; Tang, Renkuan; Yang, Junbao; Chen, Pengyu; Liu, Chao; Sun, Hongyu; He, Guanglin (Frontiers in Ecology and Evolution, 2023)
The comprehensive characterization of the fine-scale genetic background of ethnolinguistically diverse populations can gain new insights into the population admixture processes, which is essential for evolutionary and medical genomic research. However, the genetic diversity and population history of southern Chinese indigenous people are underrepresented in human genetics research and their interaction with historical immigrants remains unknown. Here, we collected genome-wide SNP data from 20 Guizhou populations belonging to three primary language families [Tai-Kadai (TK), Hmong-Mien (HM) and Tibeto-Burman (TB)], including four groups newly collected here, and merged them with publicly available data from 218 modern and ancient East Asian groups to perform one comprehensive demographic and evolutionary history reconstruction. We comprehensively characterized the genetic signatures of geographically diverse populations and found language-related population stratification. We identified the unique HM genetic lineage in Southwest China and Southeast Asia as their shared ancestral component in the demographic history reconstruction. TK and TB people showed a differentiated genetic structure from HM people. Our identified admixture signals and times further supported the hypothesis that HM people originated from the Yungui Plateau and then migrated southward during the historical period. Admixture models focused on Sino-Tibetan and TK people supported their intense interaction, and these populations harbored the most extensive gene flows consistent with their shared linguistic and cultural characteristics and lifestyles. Estimates of identity-by-descent sharing and effective population size showed the extensive population stratification and gene flow events in different time scales. In short, we presented one complete landscape of the evolutionary history of ethnolinguistically different southern Chinese people and filled the gap of missing diversity in South China.